(untitled) (PETITUM, 2025)
The research results show that (1) The legal strength of the binding sale and purchase agreement in Decision Number 221/Pdt.G/2023/PN Mks. The legal strength of the PPJB owned by the plaintiff can be said to be strong as a basis for the issuance of land rights as the object of the dispute in the decision. (2) The basis of the Judge’s consideration in decision Number 221/Pdt.G/2023/PN Mks (attached) according to the author regarding the PPJB made by the Plaintiff is that it is valid based on law because in the PPJB there are appropriate conditions which have been implemented in accordance with legal provisions and the Plaintiff is entitled to have rights in ownership of the land so that the judge’s decision regarding this matter is appropriate and valid according to law.